2006
DOI: 10.4049/jimmunol.177.6.3564
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Efficient Antitumor Immunity Using Dendritic Cells Activated by Recombinant Sendai Virus and Its Modulation by Exogenous IFN-β Gene

Abstract: Dendritic cell (DC)-based cancer immunotherapy has been paid much attention as a new and cancer cell-specific therapeutic in the last decade; however, little clinical outcome has been reported. Current limitations of DC-based cancer immunotherapy include sparse information about which DC phenotype should be administered. We here report a unique, representative, and powerful method to activate DCs, namely recombinant Sendai virus-modified DCs (SeV/DC), for cancer immunotherapy. In vitro treatment of SeV without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 37 publications
(47 reference statements)
6
77
1
Order By: Relevance
“…These tumor extracts were indeed able to block the growth of B16 cells in a type I IFN-dependent manner (Fig. S7), a finding that is consistent with previous reports showing that type I IFNs block proliferation and induce apoptosis of B16 cells (22,23). Together these data indicate that IFN-β is required for the generation of tumor-infiltrating CD8 T cells and for the antitumor activity induced by intratumoral cGAMP.…”
Section: Intratumoral Sting Activation Leads To Systemic Cd8 T-cell-msupporting
confidence: 80%
See 1 more Smart Citation
“…These tumor extracts were indeed able to block the growth of B16 cells in a type I IFN-dependent manner (Fig. S7), a finding that is consistent with previous reports showing that type I IFNs block proliferation and induce apoptosis of B16 cells (22,23). Together these data indicate that IFN-β is required for the generation of tumor-infiltrating CD8 T cells and for the antitumor activity induced by intratumoral cGAMP.…”
Section: Intratumoral Sting Activation Leads To Systemic Cd8 T-cell-msupporting
confidence: 80%
“…Second, type I IFNs may increase CD8 T-cell infiltration into cGAMP-injected tumors (6) and directly promote their survival and proliferation in the tumor microenvironment (24). However, our data suggest that the potent local antitumor efficacy is not explained by increased CD8 T-cell infiltration of cGAMP-injected tumor but rather by a direct inhibitory effect of type I IFNs on the tumor itself (22,23). Representative plots are given (Upper); each symbol represents an independent mouse (Lower).…”
Section: Discussioncontrasting
confidence: 52%
“…This result is presumably due to the low virus titer (5310 7 pfu) administered in the present study; other studies employed a higher virus titer (.1310 9 pfu). 21,34 These results indicate that the administration of BV-DCs did not impair liver and kidney functions in mice.…”
Section: Levels Of Alt Ast and Creatinine Were Not Increased In Bv-dmentioning
confidence: 68%
“…Several groups have reported that regulatory T cells (CD4 1 CD25 1 Foxp3 1 ) are induced by tumor cells and inhibit antitumor immunity, whereas other groups have reported an inhibitory effect of tumor cells that suppresses the host antitumor immune response. [32][33][34] Our data suggest that regulatory T cells may inhibit tumor growth suppression. Previously, we and other groups reported that wild-type baculovirus impairs liver function in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Target cells (YAC-1; obtained from the American Type Culture Center, Manassas, VA, USA) were labeled with 100 mCi of Na 2 51 CrO 4 for 1.5 h, and the Cr release assay was performed as described previously. 31 The percentage of specific 51 Cr release or triplicates was calculated as follows: ((experimental counts per minute (c.p.m. )Àspontaneous c.p.m.…”
Section: Nk Cell Activitymentioning
confidence: 99%